Effects of academic green space for undergraduate students / Murni Zainal and Mohd Suhail Ahmad Sahimi - Zainal, Murni; Ahmad Sahimi, Mohd Suhail (2022)
Academic Green Spaces (AGSs) are considered as an integral part of university campuses, and students can enjoy the outdoor spaces in the campus where they congregate, walk, talk, study, and relax. Aside from academic achievement, learning activities are fun yet tiring and will sometimes lead to stress, which then spurs anxiety problems. Therefore, unmanaged, and prolonged anxiety leads to depression. AGS with natural elements (such as vegetation) acts as a supportive environment that can help to reduce stress. The objectives of this research are, i) to analyse the effectiveness of AGS for the undergraduate student’s wellbeing and ii) to determine the factors of AGS that suit the undergraduate student’s interests. Quantitative methodology was applied using a case study of AGS known as Lala Land located adjacent and accessible to Annex 1 building at UiTM Perak, Seri Iskandar Campus. Close-ended questionnaires were distributed to the 50 undergraduate students (as main users of Annex 1 building and Lala Land) to identify the effect of AGS by assessing the i) physical space, ii) dimensions of “Healthy Academic Greenspace Frameworks” (HAGFs) and iii) qualities of “Perceived Sensory Dimensions” (PSDs). The results have shown that, i) the physical space is located at strategic location with easy accessibility, walkability, and adjacent to students’ facilities, accommodation, and indoor learning spaces, ii) HAGF with Symbolic space, Social space and Experienced space dimensions of the therapeutic landscape, where students feel content and reduce mental fatigue and iii) Space quality of PSDs is the most preferred because students are keen to experience spacious green spaces that are free and it is possible to find areas not crossed by roads and lots of trees. These three (3) main factors are suitable to the undergraduate student’s interests on AGS and need to be considered during planning and designing a university campus environment.